The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1207/s15327027hc1603_4
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Family Discussion on the Decision to Donate Organs: The Role of the Willingness to Communicate Scale

Abstract: Family discussion of organ donation has been found to double rates of family consent regarding organ donation. Therefore, family discussion is an important communication process to study in the effort to get more people to become organ donors. This investigation concerns the willingness to communicate about organ donation and its relationship to other variables and processes related to family discussion of organ donation. Previous research on willingness to communicate examined the antecedent variables of know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 22 publications
1
63
0
1
Order By: Relevance
“…19 Public education campaigns should continue to encourage people to become organ donors and to discuss this decision with all family members, including older children and adolescents. 20, 21 We also found that print media coverage of transplant success stories was an important and effective strategy for increasing awareness of the benefits of both organ donation and transplantation, especially in donor parents. Newspaper and magazine articles that stress how donated organs made the triumph of transplantation possible would seem to have a particularly positive impact.…”
Section: Discussionmentioning
confidence: 88%
“…19 Public education campaigns should continue to encourage people to become organ donors and to discuss this decision with all family members, including older children and adolescents. 20, 21 We also found that print media coverage of transplant success stories was an important and effective strategy for increasing awareness of the benefits of both organ donation and transplantation, especially in donor parents. Newspaper and magazine articles that stress how donated organs made the triumph of transplantation possible would seem to have a particularly positive impact.…”
Section: Discussionmentioning
confidence: 88%
“…Aynı çalışmada eğer ölen kişi gençse ve bağışı yapacak olan kişi anne-babası değil de, kardeşi ya da çocukları ise bağış izninin azaldığı saptanmıştır. Ölüm bir hastalık nedeniyle değil de bir şiddet olayı sonucu (intihar hariç) gerçekleşmişse ölen kişiye daha fazla acı çektirilmemesi düşüncesiyle yine bağış izninin azaldığı tespit edilmiştir (24).…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…Willingness to Communicate About Organ Donation Scale (developed by Morgan & Miller, 2002, extended by Smith et al, 2004). The scale measures the extent participants agree with statements related to discussing organ donation with other people on a seven-point scale (0 = Disagree Strongly; 6 = Agree Strongly).…”
Section: Willingness To Communicate About Organ Donation Participantmentioning
confidence: 99%
“…• I feel proud about my decision to donate • I would recommend the decision to become an organ donor to other people • I always want to be registered as an organ donor • I would not advise someone else to register as an organ donor (R) • I regret my decision to donate (R) • I feel very committed to my decision to become an organ donor Willingness to Communicate (Morgan & Miller, 2002;Smith et al, 2004) (0 = Disagree Strongly; 6 = Agree Strongly)…”
Section: Hedonismmentioning
confidence: 99%